MANAJEMEN PEMBINAAN KARAKTER GURU BERBASIS NILAI WAHDAH ISLAMIYAH DAN IMPLIKASINYA TERHADAP KUALITAS PEMBELAJARAN AL-QUR'AN - Ardiansyah; Bahrani Bahrani; Sudadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Teacher character development management in Islamic elementary schools is a critical yet underexplored area, particularly within organizationally affiliated institutions such as SD Al Qur'an Wahdah Islamiyah Tenggarong, East Kalimantan. This qualitative case study investigates the mechanisms of teacher character development grounded in Wahdah Islamiyah's core values, its implications for Al-Qur'an learning quality, and its alignment with the Kutai Kartanegara Regency Government's flagship program, Gerakan Etam Mengaji (GEMA), which is mandated through Peraturan Daerah No. 4 Tahun 2021. Data were collected through semi-structured interviews with the principal (Muhammad Rahman, S.Pd), vice principals, and eight classroom teachers, supplemented by classroom observation and document analysis conducted from January to March 2025. Findings reveal that the school implements a structured weekly halaqah tarbiyah every Friday, consisting of: (1) collective Al-Qur'an recitation (tilawah), (2) memorization deposit (setoran hafalan), (3) Islamic study led by gender-segregated murabbi/murabbiyah, and (4) an open sharing session. This system demonstrates a significant convergence with GEMA's objectives of building a Qur'anic community culture across all institutional levels in Kutai Kartanegara. The study finds that the school's halaqah system predates and exceeds GEMA's minimum standards, positioning it as a model of organic institutional alignment with regional religious development policy. Student achievements in azan, tahfizh, tilawah, and Islamic quiz competitions further validate the model's effectiveness. The study proposes the 'Jumat Tarbiyah Character Model' (JTCM) as a replicable framework.